Co-Integration Analysis of Exchange Rate and Inflation Effects on Economic Progress of Nigeria - Isah, Nura; Yusu, Basiru; Ibrahim, Haruna; Haruna Umar, Alhassan (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
Exchange rate fluctuations and inflation have posed the biggest challenge to Nigeria’s economy. We examined the relationships between the US dollar and the Nigerian Naira exchange rate, as well as the effects on the economic growth of Nigeria (GDP). The Dickey Fuller enhanced test was used to assess the series’ stability, and the Johansen co-integration test was applied to evaluate if the variables were co-integrated. ADF results show that the entire variables are stationary at the first difference rather than at the level. Trace statistics show that in a system with a 5% important level, there are at least two co-integrations according to the Johansen co-integration test. According to the longterm co-independence, INFR and EXR have a negative relationship with GDP, while in the short term the system has corrected its previous delays to a disbalanced position, with 58.9% quarterly growth, respectively Furthermore, the vector error correction model indicated GDP for a small-scale period was positively influenced by EXR, while INFR for a medium-scale period was significantly affected by INFR.